Analysis of Service Quality, Tax Sanctions, on Taxpayer Compliance in KP2KP Ungaran - Fudji Sri Mar’ati; Erna Sudarmawanti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
The purpose of this study is to determine whether the quality of service, the application of sanctions, is related to taxpayer compliance in KP2KP Ungaran. The type of research used is explanatory, the type of non-probability sampling technique. The sample of this research is 100 respondents of taxpayers in KP2KP Ungaran. The analytical tools used include multiple regression analysis. The test results show that service quality and tax sanctions have a positive and significant effect on taxpayer compliance. Suggestions for this study are to improve service quality and increase taxpayer knowledge of taxpayers' tax compliance